Bandwidth analysis of multimode fiber passive optical networks (PONs) - Stępniak, Grzegorz; Maksymiuk, Łukasz; Siuzdak, Jerzy (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
The analysis of frequency response in different branches of a multimode fiber based passive optical network is conducted. Both the theoretical and experimental results show that bandwidth of various network paths may be different.
Optica Applicata, Vol. 39, 2009, nr 2, s. 233-239
Keywords: optyka; multimode fibers; frequency response; bandwidth; passive optical network (PON)